RESEARCH ON DEMAND FOR BUS TRANSPORT AND TRANSPORT HABITS OF HIGH SCHOOL STUDENTS IN ŽILINA REGION (Perner's Contacts, 2017)
The paper deals with the analysis of demand for bus transport to examine determinants of demand and practices of high school students based on survey of their transport habits in Žilina Region. Transport habits of students are individual and variable in time. This group of passengers is dependent on public passenger transport services because of their travelling to schools. Significant part of demand for public passenger transport is also formed by this this group of passengers. The knowledge of student´s transport habits may help in process of adaptation of offering and quality of transport serviceability, what may subsequently stabilize demand for public passenger transport.